Security in Android (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
New technologies have always created new areas of concern for information security teams. Usually it provides time for the development of effective security controls. The rapid growth of the smartphone in market and the use of these devices for so many sensitive data have led to the emergence of security threat. A malicious user or malware on a device can create a number of risks for an organization, and so the fact that these devices are not necessarily connected does not translate to a lack of security risks. This paper will discuss why it is important to secure an Android device, what some of the potential vulnerabilities are, and security measures that can be introduced to provide a baseline of security of data on Google’s mobile OS